Knowledge and myths among Colombian teachers about high intellectual abilities (2022)
The objective of this study was to describe the knowledge and myths among Colombian teachers regarding students with High Intellectual Abilities (HIA), analyzing their relationship with sociodemographic variables of interest. A non-experimental, descriptive-correlational cross-sectional methodology was used. 584 pre-school, basic and secondary education teachers from 160 municipalities were selected through non-probabilistic sampling for participation and completed the HIA Knowledge and Myths Questionnaire. The general percentage of correct answers in the questionnaire was low and there were high levels of false beliefs primarily related to the nature of giftedness, the academic performance and achievements of these students and suitable educational interventions for this population. A relationship was found between false beliefs about HIA and the sex of participants. These results highlight the need to improve HIA training in teacher preparation. © 2022 by the authors.